Cross‐talk of alpha tocopherol‐associated protein and JNK controls the oxidative stress‐induced apoptosis in prostate cancer cells. Issue 10 (28th November 2012) - Zhu, Baoyi; Li, Xiaojuan; Zhang, Yuying; Ye, Chunwei; Wang, Yu; Cai, Songwang; Huang, Huaiqiu; Cai, Yi; Yeh, Shuyuan; Huang, Zhenhua; Chen, Ruihan; Tao, Yiran; et al.
Abstract Excess intracellular reactive oxygen species (ROS) beyond a threshold can induce apoptosis in cancer cells. However, the signal pathways that can augment the proapoptotic function of ROS remain largely unknown. We previously identified a tumor suppressor, alpha‐tocopherol‐associated protein (TAP), yet little is known regarding the role of TAP in the apoptotic signaling in prostate cancer. Interestingly, we recently found that exposure of prostate cancer cells to hydrogen peroxide (H2O2) resulted in induced apoptosis as well as increased expression of TAP. Small interfering RNA (siRNA) mediated silencing of endogenous TAP expression conferred effective protection from H2O2‐induced apoptosis. Further mechanistic study showed exposure of prostate cancer cells to H2O2 resulted in increased phosphorylation of both JNK and c‐Jun, and TAP siRNA effectively decreased H2O2‐induced JNK and c‐Jun phosphorylation. Immunoprecipitation experiments revealed that JNK physically associates with TAP. Furthermore, signaling downstream of JNK to the AP‐1 complex and BH‐3‐only subfamily were found to be regulated on changing the TAP expression status. TAP could also promote the oxidative stress‐induced apoptosis effect of docetaxel. In the mice xenograft model, H2O2 treatment induced TAP expression, JNK phosphorylation and apoptosis of prostate cancer. Recombinant adeno‐associated virus 2 (rAAV2)‐TAP injection significantly sensitizes this H2O2 proapoptotic effect. Together, we have identified a novel functional mechanism that the cross‐talk of TAP‐JNK is involved in oxidative stress‐induced apoptosis in prostate cancer cells. Disrupting the redox balance of cancer cells by this signaling may enable therapeutic selectivity and provide benefit to overcome the drug resistance of prostate cancer.